Harmonic Analysis and Neutral-Point Potential Control of Interleaved Parallel Three-Level Inverters for Flywheel Energy Storage System - Li, Zhongrui; Nie, Ziling; Xu, Jie; Li, Huayu; Ai, Sheng (Frontiers in Energy Research, 2022)
Flywheel energy storage system is a popular energy storage technology, in which inverters are the center of electrical energy conversion, directly affecting the power capacity. Parallel operation of three-level inverters is an effective approach to achieve larger motor drive power and the interleaved operation can improve the harmonic characteristics. However, harmonic analysis models of the interleaved parallel three-level inverters are rare in the literature and how the neutral-point potential imbalance affects the harmonics characteristics has not been discussed. This article establishes the harmonic calculation for balanced and unbalanced neutral-point potential through the five-level voltage capability of the interleaved parallel three-level inverters. Moreover, a neutral-point potential control method based on zero-sequence voltage injection is proposed. The implement process of the method is proposed, and how the operating frequency affect the ability of the neutral-point potential balance is studied. Finally, the simulation and experiment results verify the feasibility and practicability of the established harmonic analysis models and the neutral-point potential control method.